Primary hemostasis in fetal growth restricted neonates studied via PFA-100 in cord blood samples - Kollia, Maria; Iacovidou, Nicoletta; Iliodromiti, Zoi; Pouliakis, Abraham; Sokou, Rozeta; Mougiou, Vasiliki; Boutsikou, Maria; Politou, Marianna; Boutsikou, Theodora; Valsami, Serena (Frontiers in Pediatrics, 2022)
Background: Platelet function of Fetal Growth Restricted (FGR) neonates remains a field of debate. Platelet Function Analyzer (PFA-100) offers a quantitative in vitro assessment of primary, platelet-related hemostasis. Our aim was to examine platelet function using PFA-100 in FGR neonates and associate our results with perinatal parameters. Methods: PFA-100 was applied on 74 FGR neonates, 48 full-term (> 37 weeks’ gestation) and 26 preterm neonates (< 37 weeks). Control group consisted of 118 healthy neonates. Two Closure Times (CTs) with COL/EPI and COL/ADP cartridges were determined on cord blood samples for each subject. Statistical analysis was performed by SAS 9.4. The statistical significance level was set to 0.05 and all tests were two tailed. Results: COL/EPI CTs were prolonged in FGR (median 132s, IQR 95-181s) compared to control neonates (median 112,5s, IQR 93-145s), p=0.04. Median COL/EPI CT for term and preterm FGR neonates was 126s (IQR 90-157s) and 137s (IQR 104-203) respectively (p=0.001), and COL/ADP CT was 70s (IQR 62-80s) for term and 75s (IQR 68-82s) for preterm FGR neonates (p=0.08). Among FGR neonates, COL/EPI CT was related with delivery time (with preterm neonates exhibiting prolonged COL/EPI CTs, p=0.05). No correlation was proved between both CTs and hematological parameters in FGR neonates. Conclusions: FGR neonates showed impaired platelet function via PFA-100, with preterm FGR neonates confronting the greatest risk. Prolonged COL/EPI CTs in FGR neonates seemed to be independent of hematological parameters and could warn for closer evaluation during the first days of their lives.